Short-Term Dynamics of Bacterial Community Structure in Restored Abandoned Agricultural Soils under Semi-Arid Conditions - Natalia Rodríguez-Berbel; Rocío Soria; Ana B. Villafuerte; Raúl Ortega; Isabel Miralles (Agronomy, 2022)
The restoration of unproductive abandoned agricultural soils under a semi-arid climate in southeastern Spain was evaluated. Four organic amendments from different composted wastes (greenhouse crop residues; worm compost from sheep–cow manure and plant remains; chicken manure; and sheep–chicken manure and plant remain) were applied, untreated control plots were installed, and natural unexploited soils were selected as a reference ecosystem. Through three sampling campaigns (initial, 3 months, and 12 months), significant changes were observed in soil physico-chemical properties, nutrient content (carbon -C-, nitrogen -N-, and phosphorus -P-), and bacterial composition of the restored soils with respect to control and natural soil, especially at 3 months. The increase of labile nutrients caused the proliferation of copiotrophic phyla at 3 months, which, after their consumption, were replaced by oligotrophic phyla at 12 months. Specific taxa involved in C, N, and P cycles were identified for each soil. For the soil bacterial composition of vermicompost, only chicken and sheep–chicken manures were more dissimilar to control and natural soils after 12 months, while greenhouse crop compost showed an intermediate position between them. Results indicated that composted greenhouse crop remains could be an optimal treatment for the short-term recovery of physico-chemical properties, nutrient content, and bacterial composition of agriculture-degraded soils in semi-arid areas.